Sn-doped TiO2 nanotubular thin film for photocatalytic degradation of methyl orange dye. (December 2020) - Bjelajac, Andjelika; Petrović, Rada; Vujancevic, Jelena; Veltruska, Katerina; Matolin, Vladimir; Siketic, Zdravko; Provatas, George; Jaksic, Milko; Stan, George E.; Socol, Gabriel; Mihailescu, Ion N.; Janaćković, Djordje
Abstract: We fabricated Sn-doped TiO2 nanotubular film via annealing of anodized TiO2 nanotubes grown on F–SnO2 (FTO) glass. Annealing was carried out at 500 °C in ambient air. Anatase crystal structure was achieved with no change in nanotubular morphology in respect to as-anodized amorphous TiO2 nanotubes. The X-ray photoelectron spectroscopy analysis revealed Sn on the surface of TiO2 film, following the thermal treatment, probably caused by the diffusion from FTO glass. Depth profile examination of the film chemical composition was conducted by elastic recoil detection analysis, which showed that in addition to the diffusion of Sn from FTO, diffusion of Ti to FTO concurrently occurred. Thus, a higher concentration of Sn was found at the bottom of the tubes, while a lower concentration was present on the tubes' surface top. This explains the improved optical response revealed by a diffuse reflectance spectroscopy. The absorption enhancement demonstrated that Sn-doped TiO2 film was efficient in the degradation of methyl orange dye under visible light. Highlights: Nanotubular TiO2 film was obtained by anodization of Ti sputtered on F–SnO2 glass. XRD showed that annealing in air at 500 °C resulted in anatase phase of TiO2 . XPS and ToF-ERDA were used to investigate possible Sn diffusion from F–SnO2 . Sn-doping of TiO2 could be the reason for improved absorbance shifting to 425 nm. Sn-doped TiO2 film was shown effective in the degradation of methyl orange dye.